Real-ear measurements by probe microphone. Practical considerations - Zenker Castro, Franz (Auditio, 2021)
Measurements with a probe microphone provide an efficient and effective method in the final verification of the hearing aid fitting, since they allow the study of the electroacoustic response with the adapted mould and the hearing aid in real ear functioning. The use of these measures takes into account the individual differences of each patient and the peculiarities of a particular hearing aid and ear mould. This type of electroacoustic measurements can be carried out in all types of hearing aids, including digital ones. This article reviews in a practical way the procedures used in the clinic to obtain response measurements of the hearing aid in real ear using a probe microphone .